Kinerja Pemerintah Desa Dalam Pengelolaan Dana Desa (Studi Pada Desa Dore Kecamatan Palibelo Kabupaten Bima) - Asmawati, Ika; Basuki, Prayitno; Riva'i, Ahmad (E-Jurnal Akuntansi, 2018)
This research aimed to analyze qualitatively the performance of Village Fund execute at Dore Village Bima Regency. it is undeniable that most villages in Indonesia make village head elections in a family manner, regardless of their abilities or competencies that greatly affect their performance, as also applies in the village of Dore, Palibelo District, Bima Regency. In this study, researchers focused on the performance of village officials, not just the village head. This study used a qualitative approach, retrieval and collection of data using observation, interview, and documentation techniques to the informant as much as five (5) persons within the Performance Analysis Management of Village Fund at Dore Village Bima Regency. The research result showed that the Performance Analysis Management of Village Fund at Dore Village Bima Regency had not yet run well as from 5 (five) dimention investigated, 4(four) dimensions did not work well such as dimension of responsibility, service quality, productivity and accountability but one was only that worked well enough is responsiveness. Based on these findings, improvements such as training or courses are recommended for village officials and the provision of media as a tool to account for the management of village funds so that the performance of the Dore Village government is expected to be more optimal than before. Keywords: Productivity; Service Quality; Responsiveness; Responsibility; Accountability